Bimbingan Keagaman Yayasan Bina Mullaf Dalam Pembinaan Keagamaan para Mullaf: Studi Kasus Pembinaan Muallaf Al-Muhajirin Bumi Asri Medan - Indra Harahap; Syahira Addini; Indriani Harahap; Roza Khairunnisa; Reza Rukmana Sirait (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
he existence of the Mullaf Al-Muhajirin Bumi Asri Medan Development Foundation in Medan Helvetia District, Medan City offers new hope for converts so they no longer have to worry about carrying out Islamic teachings, no longer feel left out and certainly do not return to apostasy (return). their old religion) because they have found Islam to be a religion that brings peace to its followers. In addition, as a Muslim, the faith of a convert is good and true, so that converts who truly have strong faith are born. Judging from the nature of the investigation, this research is in the nature of a field study, an intensive examination of the context of the current situation and the ecological interactions of a unit. certain social, group, institution or community because it is seen from the researcher's thinking. goal point of view. The result of this research is the coaching procedure of Changing Al Muhajirin Earth is fun in Updating the understanding of Worshiping Changing in the Foundation, endowments Changing Al Muhajirin Earth is fun. After this consequence the first time religious instructions were given and taught in Al Muhajireen the Earth is pleasant, part of changing the consequences of the instructions per step further this religious advisory activity has a plan. To tire and develop as well as form a positive attitude and discipline as well as love of religion in different lives, you will later be people who fear Allah SWT and obey the orders of Allah SWT and His Messenger. Keywords: Guidance, Religion, Muallaf Al-Muhajirin Bumi Asri